Teologi Kematian Berdasarkan Perspektif Antropologi-Metafisika bagi Tradisi Ritual Kematian Toraja dan Jawa - Daniel Fajar Panuntun (Reformed Center for Religion and Society, 2025)
The objective of this study is to formulate a theological framework for the concept of death, utilizing the lens of metaphysical anthropology. This study serves as a scholarly reference on the preservation of death ritual traditions in Indonesia, focusing on those observed by the Torajans and Javanese. The significance of this objective lies in the inclination of the Christian tradition in Indonesia to marginalize indigenous cultural practices. This study employs the primary perspective of Gijsbert van den Brink, which is subsequently subjected to constructive analysis by the perspectives of Tibor Horvath, Robert Setio, Ebenhaizer I Nuban Timo, and Jürgen Moltmann. This study presents a theology of metaphysical anthropology of death, specifically focusing on the concept of posse mori in posse non mori. The objective is to propose a solution to preserve the death ceremonial traditions observed by the Torajans and Javanese.